PENGARUH AKUNTABILITAS, KEJELASAN SASARAN ANGGARAN DAN PARTISIPASI PENGANGGARAN TERHADAP KINERJA MANAJERIAL (Studi Pada OPD Kabupaten Lamongan) - Cindy Oktaviyanti; Ana Fitriyatul Bilgies; have zulkarnaen (Fakultas Ekonomi, 2023)
This study aims to examine the effect of accountability, clarity of budget targets, and budgetary participation on managerial performance in local government agencies in Lamongan Regency. The population in this study were all OPD offices of Lamongan Regency, totaling 21 departments. The sampling technique in this study used purposive sampling method. Data collection techniques in this research by distributing questionnaires to respondents. The questionnaires distributed were 105 questionnaires with a return rate of 89 questionnaires or 84% of the total questionnaires sent. The data were analyzed using the multiple linear regression method and processed with the SPSS Version 22 program. Based on the results of the study, it was concluded that Accountability had a positive effect on Managerial Performance in Lamongan Regency agencies, Clarity of Budget Targets had a positive effect on Managerial Performance in Lamongan Regency agencies, Budgetary Participation had an effect on Positive on Managerial Performance in Lamongan Regency Institutions. Accountability, Clarity of Budget Targets and Budgetary Participation simultaneously affect Managerial Performance in Lamongan Regency agencies.